Institutions, the cost of capital, and long-run economic growth: Evidence from the 19th century capital market - Ron Alquist; Ben Cha (Federal Reserve Bank of Chicago, 2012)
Late 19th century investors demanded compensation to invest in countries with poor institutional protection of property rights. Using the monthly stock returns of 1,808 firms located in 43 countries but traded in London between 1866 and 1907, we estimate the country-specific cost of capital. We find a negative relationship between institutions that protect property rights and capital costs. Firms located in countries with weak institutions were charged a premium compared to similarly risky firms located in countries with strong institutions, and this penalty appeared to be costly in terms of future growth. Countries that paid a premium for borrowing in London during this period grew more slowly after 1913 and are poorer today. We thus identify the capital market as a channel through which strong institutions promote growth.
Keywords: F36; G15; O16; 330; international financial integration; cost of capital; institutions; property rights; economic growth; financial development